Gigitan Ular: Manajemen Terkini - Niken Wahyu Puspaningtyas; Rismala Dewi; Ashfahani Imanadhia (Majalah Kedokteran Indonesia, 2022)
Snakebite is declared as neglected tropical disease by WHO in 2009. Limited report and collection data about the exact number of snakebite national incidents shows that this case lacking of attention. Moreover, control program, management, also proper treatment have not been understood by public and health workers. In fact, snakebite is a medical emergency that can lead to permanent disability, limb amputation, and even death. For this reason, effort are needed to reduce morbidity and mortality that arise through preventive, curative, including comprehensive understanding of related proper, safe, and effective case management.